Perancangan Sistem Informasi Indeks Kepuasan Masyarakat berbasis Android di kelurahan. - Nola Putri Ritonga; Yustria Handika Siregar (Ali Institute of Reseach and Publication, 2024)
The Kelurahan Office is a government institution at the Kelurahan or village level that is responsible for the management of public affairs in its area. His responsibilities cover various aspects, such as administrative services, population registration, community empowerment, and implementation of government programs at the local level. In addition, the sub-district office is also involved in maintaining public order, handling conflicts, and facilitating social welfare policies. Thus, the sub-district office has an important role in supporting the welfare and progress of the community at the Kelurahan or village level. Therefore, it requires an effective and efficient system for the assessment of public services. The purpose of this study is to facilitate the public in providing an assessment of public services provided, improve accessibility, transparency, and community participation and provide evaluation data for continuous improvement in the provision of public services. The system development method uses the waterfall method which includes requirements analysis, system design, implementation, testing and maintenance. The results of the study in the form of display output prove that the system is running well. And the test results of the system run well so that it can be used by the community.